Teaching Reading Through KWL (Know-Want to know-Learned) Strategy In Islamic Economics Text - Muzayyinatul Hamidia (PANYONARA: Journal of English Education, 2021)
KWL strategy is a reading strategy used by teachers or educators to improve the students' reading skills by activating their prior knowledge, encouraging their motivation, and making the student comprehend the text holistically. The purpose of this research is to (1) apply the K-W-L Strategy in Reading Islamic Economics Text (2) know How do the students apply the K-W-L strategy in reading Islamic economics text. This research is conducted in a descriptive qualitative design. The data is collected by observation and documents. Data analysis procedure based on Creswell, Rossman & Marshall, 1) Organizing and familiarizing 2) Coding and reducing 3) Interpreting and representing. The results present that the application of K-W-L strategy is made through three steps, namely 1) Pre-reading, where the teacher or researcher created a good condition of the classroom and introducing passage, and the students filling the chart in K column 2) Whilst reading, the teacher leads the student read the text and started to write down what they want to learn in W column 3) Post-reading in which the students started to comprehend the passage, make a conclusion and stated what they have learned from text based on their comprehension in L column. The study also concluded that the KWL strategy was appropriate in teaching reading on Islamic Economics Text, and it can be applied in reading for any level of English learners.